Edukasi mengenalkan pemantauan perkembangan anak dengan Kuesioner Pra Skrining Perkembangan (KPSP) pada kader posyandu - Suparno, Suparno; Estiani, Meilina; Suryanda, Suryanda (Indonesia Berdaya, 2024)
The existence of a child development disorder is an important reason for monitoring child development as early as possible. In the preliminary survey, it was found that children with speech/language delays reached 0.02%. Early detection of developmental disorders in children has an important role in the welfare of children and families. And the fact states that early detection of developmental disorders must be available in primary child health services. Monitoring of children's development can be done using the Developmental Pre-screening Questionnaire. Kader posyandu as part of primary service personnel need to be given training in monitoring child development with this questionnaire so that it can be applied to Posyandu activities for toddlers. The problem in this activity is that the kader posyandu in Desa Talang Jawa wilayah kerja Puskesmas Tanjung Agung, Kecamatan Baturaja Barat, have never received information and have not had the ability to use this Pre-screening Development Questionnaire. This educational activity aims to increase knowledge and skills about monitoring children's development using the Developmental Pre-screening Questionnaire. From this activity, it was found that the level of knowledge of participants before education was 7.4% enough, 92.6% less, and after being given education was Good 63 %, 25.9% enough and 11.1% less. The ability of participants after being given education increased by 100%. It was concluded that after the education introduced the monitoring of children's development with the Developmental Pre-screening Questionnaire, there was an increase in the knowledge and ability of kader posyandu